Comprehensive autophagy evaluation in cardiac disease models. Issue 3 (27th August 2019) - Kaludercic, Nina; Maiuri, Maria Chiara; Kaushik, Susmita; Fernández, Álvaro F; de Bruijn, Jenny; Castoldi, Francesca; Chen, Yun; Ito, Jumpei; Mukai, Risa; Murakawa, Tomokazu; Nah, Jihoon; Pietrocola, Federico; et al.
Abstract: Autophagy is a highly conserved recycling mechanism essential for maintaining cellular homeostasis. The pathophysiological role of autophagy has been explored since its discovery 50 years ago, but interest in autophagy has grown exponentially over the last years. Many researchers around the globe have found that autophagy is a critical pathway involved in the pathogenesis of cardiac diseases. Several groups have created novel and powerful tools for gaining deeper insights into the role of autophagy in the aetiology and development of pathologies affecting the heart. Here, we discuss how established and emerging methods to study autophagy can be used to unravel the precise function of this central recycling mechanism in the cardiac system.